The ethics of blood testing as an element of doping control in sport - Brown A.; Lachance, V.; Pipe, A. (Medicine & Science in Sports & Exercise, 1999)
Sport authorities continue to confront a variety of perplexing issues as they attempt to address effectively and efficiently the problems posed by doping. The emergence of the phenomena of blood doping and the administration of erythropoietin have added to the challenges faced by doping control authorities. Some sport organizations have introduced blood tests in an attempt to deal with these issues despite the absence of any effective test for the detection of the administration of homologous blood products or eythropoietin. A number of ethical issues are raised by such developments. Even in the presence of an effective test it is suggested that the decision to implement a specific testing approach can be reached by considering the wishes of a hypothetical "Fair Competitor" and an analysis of the costs involved. In this respect the Fair Competitor assumes in the sport community the role that the "reasonable person" occupies in law, permitting an analysis of a proposed course of action. In making any decision regarding the implementation of any test, a Fair Competitor would be guided by considerations of the postulated advantage and incidence of a doping technique, the likelihood of false positive and negative results, the risk of unwanted consequences of a testing process, and a concern that a specific test not accelerate the likelihood of the use of other doping methods. This approach is applied to a consideration of the appropriateness of blood testing in sport. It is concluded, using such an analysis, that in their present state of development, blood tests should not be implemented. It is recognized that certain sport authorities currently use blood tests to exclude competitors whose blood values exceed certain predetermined levels on the grounds of concerns regarding health and safety. Screening of this kind is beyond the purview of this discussion.